Patient characteristics and the therapist as predictors of depressed patients' outcome expectation over time: A multilevel analysis. (30th September 2019) - Vîslă, Andreea; Flückiger, Christoph; Constantino, Michael J.; Krieger, Tobias; Grosse Holtforth, Martin
Abstract: Objective: Although there is an established link between patients' early positive outcome expectation for and their actual improvement from therapy, there is little research on patients' change in outcome expectation across therapy and both patient and therapist correlates of early outcome expectation level and change. The present study examined: (i) the overall trajectory of change in patients' outcome expectation through cognitive-behavioral therapy (CBT) for depression; (ii) patient characteristics as predictors of both initial outcome expectation and change in outcome expectation; and (iii) between-therapist effects in outcome expectation change. Method: Depressed patients ( N = 143) received a brief course of CBT. Outcome expectation was measured at screening, pretreatment, session 7, and session 14. Results: Outcome expectation linearly increased from screening to session 14. When controlling for other patient characteristics at intake, having previous depressive episodes was negatively associated with initial outcome expectation and higher well-being was positively associated with initial outcome expectation. When controlling for early alliance and early symptom change, outcome expectation change was predicted by previous depressive episodes. Finally, therapist effects emerged in outcome expectation over time. Conclusions: Various depressed patients' characteristics predict initial outcome expectation level and change, with significant between-therapists' differences related to outcome expectation change.